Parallel unstructured multigrid method for numerical simulation of compressible and incompressible viscous flows - Tai, Chin Hoe (2008)
The thesis presents the development and validation of an unstructured multigrid method and parallelization of single grid and multigrid codes for the study of both compressible and incompressible viscous flow.